Duplication of the transverse colon in adults: a case report and literature review - Zhang, Xiaochun; Di, Guangci; Cheng, Wei; Wang, Cuizhong; Gong, Guanwen; Jiang, Zhiwei (Frontiers in Oncology, 2023)
ORCID number: Xiaochun Zhang (0009-0000-3644-5333). Background: Duplication of the transverse colon is a rare gastrointestinal malformation. Its pathogenesis is still unclear, and it is extremely rare in adults. Patients often present with symptoms of tumor compression such as abdominal mass, abdominal pain, and constipation as the first manifestation.A patient with a duplication of the transverse colon was admitted to the Department of General Surgery of our hospital.Laparoscopic exploration found a mass at the rear of the transverse colon near the splenic flexure, and the root was connected to the middle portion of the transverse colon.Surgery is a radical treatment and reduces the possibility of perforation, bleeding, obstruction, and cancer.